Newer Oral Anticoagulant Therapy – Prospects and Practices: A Review - Morries, Lancy; Mariya, Niya; Joseph, Joel Joby; Abraham, Suja (Indian Journal of Pharmacy Practice)
The conventionally used anticoagulants for the treatment of thromboembolism include unfractionated heparin, low molecular weight heparin, fondaparinux and Vitamin K antagonists such as warfarin, phencoumarol. Though they were considered the milestones in anticoagulation therapy, their use in clinical practice is limited due to its certain patient related issues such as wide variations in dose response relationship, delayed onset and offset of action, narrow therapeutic range of clinical effectiveness, frequent monitoring and dose adjustment. In order to overcome the above drawbacks of conventional anticoagulants, FDA approved Newer Oral Anticoagulants that provide stable anticoagulation at a fixed dose without the need for laboratory control, making it more convenient therapeutic regimen. In this review, the use of newer oral anticoagulant drugs in current clinical practice as well as the facts and concerns related to its use, safety and efficacy in patients with concomitant diseases like antiphospholipid syndrome, chronic kidney disease and patients undergoing cardio version is focused. Moreover, the various newer developments and ongoing trials in the field of anticoagulation were also discussed. The emergence of new reversal agents that are currently under development and its role in paediatric populations will be also an added advantage for its development. In short, the use of new anticoagulants had shown improvements in safety and efficacy as well as they offer greatest promise and opportunity for the replacement of Vitamin K Antagonists and other conventional agents.
Keywords: Apixaban; Betrixaban; Dabigatran; Edoxaban; Newer oral anticoagulants; Rivaroxaban.